UPAYA PENINGKATAN KESEHATAN TENTANG BAHAYA HIPERKOLESTEROLEMIA - Salvita Fitrianti; Miko Eka Putri; Rahmi Dwi Yanti (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
High cholesterol levels are one of the causes of metabolic problems that cause heart disease, blood vessels, and diseases that are associated with blockages in blood vessels. The accumulation of the amount of fat deposits on the walls of blood vessels can cause a blockage in the blood vessels or known as atherosclerosis. The purpose of this service is to increase people's knowledge about the dangers of cholesterol. This service was carried out in December 2018 at the home of the RT 05 Payo Sigadung house. The target of this activity is Payo Sigadung RT 05 Rawa Sari Village. Activities consist of several processes 1). Check cholesterol levels, 2). Pre-test the public's knowledge about the dangers of hypercholesterolemia, 3) Conduct health education, 4) Perform a test of knowledge test after being given a health education about cholesterol. The output of this activity is 1). People who take counseling are expected to be able to understand the effects of high cholesterol and cholesterol signs, 2) Results of checking cholesterol levels. The results of the implementation of this activity were 85% of the community were able to answer questions given and understand about hypercholesterolemia. With the increase in public knowledge about the dangers of hypocholesterolemia, it is hoped that the community will be able to implement maintaining the health of most foods so that they can avoid hypercholesterolemia